2014
DOI: 10.1371/journal.pone.0096857
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Profiling of microRNAs and Their Target Genes from Developing Caprine Skeletal Muscle

Abstract: Goat is an important agricultural animal for meat production. Functional studies have demonstrated that microRNAs (miRNAs) regulate gene expression at the post-transcriptional level and play an important role in various biological processes. Although studies on miRNAs expression profiles have been performed in various animals, relatively limited information about goat muscle miRNAs has been reported. To investigate the miRNAs involved in regulating different periods of skeletal muscle development, we herein pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 74 publications
(87 reference statements)
6
30
0
Order By: Relevance
“…In this work, a total of 410 known goat miRNAs and 752 goat miRNA homologs were identified across the four developmental stages studied. Some of the expressed miRNAs identified here have already been reported in different species [3, 14, 16, 21, 38], indicating similar molecular mechanisms underlying skeletal muscle development in animals. For instance, eleven and nine of the most abundant miRNAs (over 10000 RPM), including the myomiRs, were among the top 20 abundantly expressed miRNAs detected during skeletal muscle development in porcine [14] and Xuhuai goat [21], respectively.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In this work, a total of 410 known goat miRNAs and 752 goat miRNA homologs were identified across the four developmental stages studied. Some of the expressed miRNAs identified here have already been reported in different species [3, 14, 16, 21, 38], indicating similar molecular mechanisms underlying skeletal muscle development in animals. For instance, eleven and nine of the most abundant miRNAs (over 10000 RPM), including the myomiRs, were among the top 20 abundantly expressed miRNAs detected during skeletal muscle development in porcine [14] and Xuhuai goat [21], respectively.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies in livestock have demonstrated that many miRNAs are highly expressed in prenatal stages and thus are thought to play important roles in skeletal myogenesis [12, 14, 16, 21]. In this work, a total of 410 known goat miRNAs and 752 goat miRNA homologs were identified across the four developmental stages studied.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In goat skeletal muscle, the main focus has been on genes and miRNAs rather than on lncRNAs [44, 45, 50, 51]. In the present study, we identified a total of 3981 multiple exon lncRNAs in fetal and postnatal goat skeletal muscle.…”
Section: Discussionmentioning
confidence: 83%